30.4k views
5 votes
Nathaniel is using the quadratic formula to solve 0 = x2 + 5x - 6. His steps are shown below. Table showing 3 steps to solve an equation using the quadratic formula. What are the solutions to the equation?

2 Answers

2 votes

Answer:

Step-by-step explanation: Answer is B-6,1

User Dan VanWinkle
by
5.0k points
4 votes

Answer:


\underline{x\in\left\{-6\,,\ 1\right\}}

Explanation:


x^2+5x-6=0\\\\a=1\,,\ \ b=5\,,\ \ c=-6\\\\x_1=(-5-√(5^2-4\cdot1\cdot(-6)))/(2\cdot1)=\frac{-5-√(25+24)}2=\frac{-5-√(49)}2=\frac{-5-7}2=-6\\\\x_2=(-5+√(5^2-4\cdot1\cdot(-6)))/(2\cdot1)=\frac{-5+7}2=1

User Eriks Dobelis
by
4.3k points